Oat agriculture, cultivation and breeding targets: implications for human nutrition and health. (30th September 2014) - Stewart, Derek; McDougall, Gordon
Abstract : Oats are undervalued in comparison with wheat, rice and barley, despite their unique composition that includes many of the nutrients required for health and a reduced risk of degenerative disease incidence. Furthermore, oats as whole grain and some of their associated products also contain β-glucan, a complex polysaccharide that has an approved health claim to reduce blood cholesterol levels and reduce the risk of CHD incidence if consumed at ≥ 3 g/d. At the agronomic level, oats exhibit optimal growth in regions of moderate temperature and long day length. In addition, they can tolerate wet weather and acidic soils more effectively than other cereals, such as wheat. Studies have shown that there is diversity in the content and composition of nutrients and health-beneficial components within the available wild and cultivated germplasm and that these are amenable to be enhanced by different agronomic practices as well as are susceptible to climatic variation. The advances in modern plant genetics, developed in sister cereals such as wheat, rice and barley, mean that oat development and exploitation should see an acceleration in the coming decade as they are adopted and applied. These advances include approaches such as genome sequencing, genotyping by sequencing and the allied next-level analytical approaches of RNA sequencing, transcriptome profiling and metabolomics. The collation and coordination of these approaches should lead to the generation of new, tailored oat varieties that are nutritionally enhanced and contain a greater proportion of health-beneficial components that can be translated through into a wide(r) range of consumer products with the ultimate hope of associated benefits to human health and nutrition.